Linguistic complexity in high-school students’ EFL writing - Delić, Amer; Jahić Jašić, Alma (ExELL, 2025)
This study examined the syntactic and semantic complexity of L2 English writing in a Bosnian- Herzegovinian high school. Forty texts written by individual students, ten per grade, were quanti-tatively analyzed by applying methods established in previous research. The syntactic portion of the analysis, based on the t-unit analysis introduced by Hunt (1965), was done using the Web-based L2 Syntactic Complexity Analyzer (Lu, 2010), while the semantic portion, largely based on the theory laid out in systemic functional linguistics (Halliday & Matthiessen, 2014), was done using the Web-based Lexical Complexity Analyzer (Ai & Lu, 2010) as well as manual identifica-tion of grammatical metaphors. The statistical analysis included tests of variance, correlation, and effect size. It was found that the syntactic and semantic complexity of writing increases in later grades; however, this increase is not consistent across all grades.